Hubungan antara Iman Katolik dengan Kepercayaan Orang Manggarai dalam Terang Konstitusi Dogmatis Nostra Aetate - Ignasius Alvedo Hasan; Agustinus Risno; Jilbertus Fernando Samo Langoarang; Yohanes De Ngedu; Adrianus Banao; Yalentus Woni (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
A crucial issue currently facing the Church is its stance on building good and harmonious relationships with all other belief systems within its own community. Although dogmatically the Church explicitly expresses its openness to all religious practices and piety lived out by the faithful according to their traditional beliefs, the Church remains cautious so that in building relationships through dialogue, the traditions of the Church are not lost. This paper aims to highlight the relationship between the Catholic faith and the traditional belief system of the Manggarai people in light of the dogmatic constitution Nostra Aetate. Nostra Aetate is one of the key documents resulting from the Second Vatican Council that addresses the current reality of religious diversity. Through this document, the Church seeks to declare its commitment to reflecting on the fact that all humanity shares a single origin and a single ultimate goal: God Himself. The beliefs or religious system of the Manggarai people is implicitly monotheistic, namely Mori Jari dedek Ema pu’un kuasa. On this basis, the Church sees that the same concept exists in Catholic doctrine. In this study, the author uses qualitative research with a text analysis approach. Text analysis is a methodology in qualitative research that aims to interpret and analyze texts based on their context.